2020
DOI: 10.1007/s42770-020-00328-8
|View full text |Cite
|
Sign up to set email alerts
|

Canine sporotrichosis: polyphasic taxonomy and antifungal susceptibility profiles of Sporothrix species in an endemic area in Brazil

Abstract: Sporotrichosis, a mycosis caused by pathogenic species of the genus Sporothrix, affects diverse species of mammals. Until 2007, Sporothrix schenckii was considered the unique etiologic agent of sporotrichosis. Canine sporotrichosis is a poorly reported disease, and the majority of cases are from Rio de Janeiro, Brazil. There are scarce studies on the characterization of canine isolates of Sporothrix schenckii complex, as well as few antifungal susceptibility data available. The aim of this study was to charact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 17 publications
(25 citation statements)
references
References 60 publications
2
23
0
Order By: Relevance
“…However, other studies investigating human, feline, and canine isolates of Sporothrix sp. from Brazil have identified other species, including S. schenckii sensu stricto in a canine case [ 71 ], in feline cases [ 43 , 72 ], and in humans [ 20 , 34 ], as well as S. luriei in a canine case [ 43 ], and S. globosa only in humans [ 73 ]. The description of other Sporothrix species from Brazil, including in dogs and humans from the same geographical region of this study, indicates that they may be circulating among cats in Rio de Janeiro; however, these other Sporothrix species in cats from this region have not yet been confirmed.…”
Section: Discussionmentioning
confidence: 99%
“…However, other studies investigating human, feline, and canine isolates of Sporothrix sp. from Brazil have identified other species, including S. schenckii sensu stricto in a canine case [ 71 ], in feline cases [ 43 , 72 ], and in humans [ 20 , 34 ], as well as S. luriei in a canine case [ 43 ], and S. globosa only in humans [ 73 ]. The description of other Sporothrix species from Brazil, including in dogs and humans from the same geographical region of this study, indicates that they may be circulating among cats in Rio de Janeiro; however, these other Sporothrix species in cats from this region have not yet been confirmed.…”
Section: Discussionmentioning
confidence: 99%
“…Nakasu et al [6] describe the therapeutic history of feline cases infected by itraconazole-resistant S. brasiliensis isolates in an endemic region of Southern Brazil. On the other hand, canine sporotrichosis is a poorly reported disease, and the majority of cases are from Rio de Janeiro, Brazil, as described here by Boechat et al [7]. The authors report a S. schenckii infection in dogs, in the state of Rio de Janeiro, Brazil.…”
mentioning
confidence: 56%
“…Most isolates were reported from South America ( n = 216 or 81%), followed by Asia ( n = 28 or 10%), and Central America and Oceania ( n = 1 or 0,37%) less frequently. After the description of new species of the genus Sporothrix, the identification of clinical isolates has been carried out worldwide, especially in regions where a large number of sporotrichosis cases occurs ( Boechat et al., 2021 ), such as in southeastern Brazil, considered a zoonotic epidemic area of sporotrichosis ( Gremião et al., 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…When we refer to dogs, other important domestic animals with strict relationship with humans, only Italy (S. mexicana) and Brazil (S. brasiliensis, S. schenckii and S. luriei) samples of these animals were isolated in our study, as shown by Boechat et al. (2021) and Viana et al.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation